evaluation of thecounseling and guidance Process in school by the counseling and guidance advisors - titraoui, radhouane (Journal of Social Sciences and Humanities, 2020)
This study aimed to assess the process of guidance and counseling advisors within Algerian educational institutions, by examining the opinions of guidance and counseling advisors on this process, where the field application procedures for this study were conducted on to a sample consisting of 35 from 42 advisors who represent The original study population, followed to the Center of School and Vocational Guidance in M’silain the year 2012; where they were questioned by distributing a questionnaire consisting of 24 items distributed on threeaxes: (school media / psychological counseling / school guidance), and this after confirming its psychometric characteristics;In order to address and analyze the results of our study, we have adopted the method of percentages, which finally led us to a set of results according to which the process of guidance and counselingin our educational institutions is carried out weakly, but it is not possible to ignore some noticeable improvement in the level of media services, In addition to the counselors tendency to better take care of students desires than before, despite their inability to eliminate the educational map system, and the policy of filling pedagogical spots imposed by the central administration on them;Therefore, reconsidering the reality of the current guidance is a necessity that imposes itself, in order to exit this activity from its organizational - administrative - form to the field of pedagogical practice, as well as to think about reconsidering the final evaluation methods in order to overcome the evaluation that places the student in the circle of school marks that often What is difficult to explain, especially when it is the only and fundamental criterion according to which decisions are taken that determine the course and the scholastic fate of the student